The Influence of Internship Experience and Work Motivation on Work Readiness in Final Year Students of the Faculty of Economics, Wiralodra University, Indramayu - Sonia Febiana; Nurjanah Rahayuningsih; Ardika Sulaeman (Electronic Journal of Education, Social Economics and Technology, 2025)
Improving Internship work experience and work motivation is important to enhance students ' self-potential and train work readiness. This research is motivated by low work readiness and work Motivation. Internship work experience and work motivation is knowledge or skills acquired from practical work in the business or industrial world for a certain period. The problem formulation in this study is how internship work experience and work motivation influence the work readiness of the Faculty of Economics students at Wiralodra Indramayu University in the 8th semester. The purpose of this research is to determine the influence of internship work experience and work motivation on the work readiness of the Faculty of Economics students at Wiralodra Indramayu University in the 8th semester who have undertaken internships at various institutions. The method used in this research is a quantitative approach with a data collection technique, one of which is a questionnaire given to students of the Faculty of Economics, Wiralodra Indramayu University, who have undertaken internships as a sample in the study. The sample used in this study consisted of 60 respondents. The data source used is primary data, and the data were processed using SPSS 26. The analysis methods used include classical assumption tests, simple and multiple linear analysis, T- test, F- test, and coefficient of determination test (R2). This research uses internship work experience indicators as an independent variable (X1) and work motivation as an independent variable (X2), as well as work readiness as the dependent variable (Y). The results of the research using the F- test show that internship practice experience and work motivation simultaneously have a significant effect on work readiness with a significance value of 0.000 0.05. Based on the t- test or partial test, internship work experience has a significant effect on work readiness with a significance value of 0.000 0.05, while work motivation has a significant effect on work readiness with a significance value of 0.000 0.05. The magnitude of the influence of internship work experience and work motivation on the work readiness of the Faculty of Economics students at Wiralodra Indramayu University is 0.494, equal to 49.4%.